Factors Affecting Dividend Policy Are Influenced By Profitability, Liquidity, And Leverage Using Gcg As A Moderating Variable In The Financial Sector In Indonesia - Akhmad Ravi Eka Baharsyah; Hartono; Yuliasnita Verlandes (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
This study investigates the effect of profitability, liquidity, and leverage on dividend policy in the Indonesian banking sector, with Good Corporate Governance (GCG) as a moderating variable. Employing a quantitative approach, the research utilizes multiple linear regression and Moderated Regression Analysis (MRA) on secondary data derived from the annual financial reports of ten banks with the highest dividend ratios listed on the Indonesia Stock Exchange (IDX) during 2023–2024. The findings indicate that profitability, liquidity, and leverage do not have a significant influence on dividend policy. Moreover, GCG does not exhibit a moderating effect on the relationship between the independent variables and dividend policy. These results highlight that dividend policy in Indonesian banks is more strongly determined by industrial regulations, expansion strategies, and macroeconomic conditions rather than internal financial indicators. The study contributes to the literature by providing empirical evidence from the banking sector in emerging markets and offers practical insights for policymakers, investors, and corporate managers in formulating dividend distribution strategies.